PENINGKATAN KETERAMPILAN MENYIMAK PROSA ANAK MENGGUNAKAN MEDIA AUDIO KELAS V SD MUHAMMADIYAH 2 PONTIANAK - Permatasari, Nur Indah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract The common problem of this research was to know how audio media can improve listening child prose skills for students grade V Primary School Muhammadiyah 2 Pontianak. The common purpose of this research was to describe how audio media can improve listening child prose skills for students grade V Primary School Muhammadiyah 2 Pontianak. The method that used in this research was descriptive method with a form of classroom action research. The subject in this research were 40 students of class VD. The procedure in this research consists of four step: planning, action, observation, and reflection. The data collection technique that used in this research were direct observation technique and scrutiny documents. The data collection technique that used in this research were observation sheets and sheets of scrutiny documents. This research result: (1)The teachers planning learning ability is very good because on first cycle is 3,87 and on second increase to 3,90. (2) The teachers doing learning ability is very good because on first cycle is 3,77 and on second increase to 3,78. (3) Enhacement listening child prose skills using audio media is good because on first cycle the average students score is 77,10 and on second increase to 84,68. Keywords: Listening Skills, Child Prose, Audio Media Â